Star wars. Last shot - Older, Daniel José (Del Rey, 2018)
It's been 10 years since the rebel hero Han Solo last encountered Fyzen Gor. After mounting a successful rebellion against the Empire and starting a family with an Alderaanian princess, Han hasn't given much thought to the mad inventor. But when Lando turns up at Han's doorstep in the middle of the night, it's Fyzen's assassins that he's running from. And without Han's help, Lando - and all life on Cloud City - will be annihilated. With the assistance of a young hotshot pilot, an Ewok slicer prodigy, the woman who might be the love of Lando's life, and Han's best and furriest friend, the two most notorious scoundrels in the New Republic are working together once more. They'll have to journey across the stars - and into the past - before Gor uses the device's power to reshape the galaxy.